Exchange Rate Pass-through into German Import Prices – A Disaggregated Perspective - Joscha Beckmann; Ansgar Belke; Florian Verheyen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This study analyzes the exchange rate pass-through into German import prices based on disaggregated data taken on a monthly basis between 1995 and 2012. Our main contribution is twofold: firstly, we employ various time-series techniques to analyze data for different product categories, and also cointegration techniques to carefully distinguish between shortrun and long-run pass-through coefficients. Secondly, in a panel data approach we estimate time-varying pass-through coefficients and explain their development with regard to various macroeconomic factors. Our results show that long-run pass-through is only partly observable and incomplete, while short-run passthrough shows a more unique character, although heterogeneity across product groups does exist. We are also able to identify several macroeconomic factors which determine changes in the degree of pass-through, which is especially relevant for policymakers. – – Diese Arbeit untersucht, inwieweit sich Wechselkursänderungen in deutschen Importpreisen niederschlagen. Als Datengrundlage dienen disaggregierte Importpreisindizes für den Zeitraum 1995-2012. Wesentliche Beiträge dieser Analyse liegen einerseits in der sorgfältigen Analyse der kurz- und langfristigen Effekte. Andererseits wird in einem zweiten Schritt versucht, im Rahmen eines Panelansatzes die Entwicklung der geschätzten Koeffizienten zu erklären und somit die Bestimmungsgründe der Wechselkursweitergabe zu ermitteln. Die Ergebnisse zeigen, dass die langfristige Weitergabe unvollständig ist und auch nicht in allen Fällen eine stabile Langfristbeziehung etabliert werden kann. Die kurzfristigen Effekte sind weitaus homogener. Darüber hinaus zeigt sich, dass die Weitergabe von Wechselkursänderungen mit steigender Unsicherheit zunimmt.
Keywords: E31; F10; F14; 330; exchange rate pass-through; germany; cointegration; time-varying; coefficient model